Effect of Covid-19 related Stress on Marital Quality during Covid-19 Pandemic - Budiartini, Ni Nyoman (Psychological Research and Intervention, 2021)
This research aimed to understand the effect of stress during the pandemic on marital quality in Bali. This research used a quantitative approach. Subjects involved in this research were 242 people who had been married for at least five years, with intact family conditions, and lived in Denpasar City, Bali. The instruments in this research were the COVID Stress Scale from Taylor (2020) and the Marital Quality scale arranged by Nurhayati (2017). The validity of this research used content validity by expert judgment. Reliability in the scale of this research used the Cronbach Alpha reliability coefficient. The COVID stress variable has a reliability of 0.934, while the variable of marital quality has a reliability of 0.889. As for the data analysis, descriptive analysis and simple linear regression analysis were used. Based on the data analysis, the regression coefficient was 0.028 and sig. 0.307, with the value of R square = 0.004. The results showed that COVID stress does not affect the marital quality in Bali.